Development of a Scratch-Based Interactive Educational Game (Gesabat) to Enhance Learning Motivation and Mathematical Thinking Speed Among Junior High School Students - Dwi Rubiyanto; Nur Fajrie; Eko Darmanto (Universitas Mohammad Husni Thamrin, 2026)
This study aims to develop a Scratch MIT-based educational game media called Gesabat on basic integer operations for seventh-grade junior high school students in Pecangaan District, as well as to test its level of validity, practicality, and effectiveness in improving students' learning motivation and thinking speed. The research method used is Research and Development (R&D) with a modified 4-D model (Define, Design, Develop, Disseminate) on a limited dissemination scale. The research subjects consisted of 4 expert validators, mathematics teachers, and 150 seventh-grade students from four junior high schools in Pecangaan District selected using Cluster Random Sampling technique. The expert validation results showed an final average feasibility of 93.8% (Very Feasible) with an Aiken’s V coefficient of 0.92 (Very Valid). In the practicality aspect, the media was declared very practical because it could be operated autonomously in offline mode using Scratch Desktop. The effectiveness test through Paired Samples T-Test on a large-scale field trial (N = 150) showed an increase in the average learning motivation from 23.97 to 29.80 (t = -19,800; p < 0,001) with a Cohen's d effect size of 1.62 (very large effect). Students' cognitive thinking speed parameters also shot up significantly from an average of 25.10 to 32.71 (t = -27,264; p < 0,001) with a Cohen's d effect size of 2.23. These results conclude that the integration of the Scratch-based Gesabat educational game is valid, practical, and significantly effective in optimizing seventh-grade students' affective motivation and numeracy thinking speed.